2013
DOI: 10.1088/1468-6996/14/5/055005
|View full text |Cite
|
Sign up to set email alerts
|

Material design of plasma-enhanced chemical vapour deposition SiCH films for low-kcap layers in the further scaling of ultra-large-scale integrated devices-Cu interconnects

Abstract: Cap layers for Cu interconnects in ultra-large-scale integrated devices (ULSIs), with a low dielectric constant (k-value) and strong barrier properties against Cu and moisture diffusion, are required for the future further scaling of ULSIs. There is a trade-off, however, between reducing the k-value and maintaining strong barrier properties. Using quantum mechanical simulations and other theoretical computations, we have designed ideal dielectrics: SiCH films with Si–C2H4–Si networks. Such films were estimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…[402][403][404][405] Shimizu's results using precursors such as 1,1-divinyl silacyclopentane (DVScP) and 5-silaspiro- [4,4]-nonane (SSN) have shown that a-SiC:H films with a significant improvement in mass density can be achieved for a given dielectric constant relative to a-SiC:H films deposited using traditional tetramethylsilane (4MS) precursors. 403 Using similar precursors, 100 nm a-SiC:H films with k values as low as 3.1 that show Cu diffusion barrier performance equivalent to higher k = 5.0 a-SiCN:H have also been demonstrated.…”
Section: Future Trends and Research Needed For Low-k Db And Es Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…[402][403][404][405] Shimizu's results using precursors such as 1,1-divinyl silacyclopentane (DVScP) and 5-silaspiro- [4,4]-nonane (SSN) have shown that a-SiC:H films with a significant improvement in mass density can be achieved for a given dielectric constant relative to a-SiC:H films deposited using traditional tetramethylsilane (4MS) precursors. 403 Using similar precursors, 100 nm a-SiC:H films with k values as low as 3.1 that show Cu diffusion barrier performance equivalent to higher k = 5.0 a-SiCN:H have also been demonstrated.…”
Section: Future Trends and Research Needed For Low-k Db And Es Materialsmentioning
confidence: 99%
“…Continued k scaling in Si-O-C-N system.-One interesting method that has been recently described by Shimizu attempts to utilize the incorporation of long Si-(CH 2 ) x -Si networks to achieve both a reduction in k and improvement in diffusion barrier performance for a-SiC:H thin films. [402][403][404][405] Shimizu's results using precursors such as 1,1-divinyl silacyclopentane (DVScP) and 5-silaspiro- [4,4]-nonane (SSN) have shown that a-SiC:H films with a significant improvement in mass density can be achieved for a given dielectric constant relative to a-SiC:H films deposited using traditional tetramethylsilane (4MS) precursors. 403 Using similar precursors, 100 nm a-SiC:H films with k values as low as 3.1 that show Cu diffusion barrier performance equivalent to higher k = 5.0 a-SiCN:H have also been demonstrated.…”
Section: Future Trends and Research Needed For Low-k Db And Es Materialsmentioning
confidence: 99%
“…Therefore we can assume that the results of the silicon, nitrogen, carbon and oxygen content in silicon carbonitride films obtained by using the EDS are authentic. It should be noted that, according H. Shumizu et al, 3,59 the increased carbon content in the films with the ratio (C/Si ∼ 4) leads to the resistance against the plasma damage, decrease of porosity and improvement of barrier properties against copper diffusion.…”
Section: 51mentioning
confidence: 95%
“…One can mention that the measured dielectric constants 4.4-4.5 are low than the typical values observed for silicon carbonitride barrier layers developed for interconnect application (4.8-5.8). 1 H. Shimizu et al 59 showed that a lower porosity, i.e. highly packed atomic arrangement, improves the barrier properties against Cu diffusion.…”
Section: 51mentioning
confidence: 99%
“…The increase in mechanical strength in hydrocarbon crosslinks was higher than in –O‐ bridges. Extensive studies are continuing to be conducted in the views of material design, for instance, written by Shimizu et al…”
Section: Materials Bond Engineering Of Siocmentioning
confidence: 99%